2009
DOI: 10.1186/2047-783x-14-8-359
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of circulating tumour cells and its correlation with tumour stage in breast cancer patients

Abstract: Background Breast cancer (BC) represents one of the leading causes of cancer related deaths worldwide. New tools for diagnostic staging and therapeutic monitoring are needed to improve individualized therapies and improve clinical outcome. The analyses of circulating tumour cells may provide important prognostic information in the clinical setting. Materials and methods Circulating tumour cells (CTC) of 63 BC patients were isolated from peripheral blood (PB) through imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The immunocytochemical detection of FPTCs turned out to be an independent additional strong prognostic factor as also described in other tumor entities before [ 22 - 24 ]. The short survival time of these patients is similar to patients with an M1-disease [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 59%
“…The immunocytochemical detection of FPTCs turned out to be an independent additional strong prognostic factor as also described in other tumor entities before [ 22 - 24 ]. The short survival time of these patients is similar to patients with an M1-disease [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 59%
“…23 Moreover, it was accompanied by elevation of CTCs in cases of lung cancer, breast cancer, urothelial carcinoma and gastric cancer. [24][25][26][27][28] Since 2004, a number of CTCs has been approved by the FDA to evaluate the ecological prognosis and outcome. In the current study, it was shown that the higher the number of CTCs in the serum, the worse the prognosis for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…This characterization could give hints towards cancer prognosis. For example, Bölke et al described in 2009 [ 57 ], that the expression of certain genes is related to advanced breast cancer stages. Additionally, a characterization of CTCs could help to personalize treatment by increasing efficiency and reducing side effects, resulting in a better outcome and an increased survival, rendering great benefit to the patients.…”
Section: Conclusion and Future Prospectivementioning
confidence: 99%